2015
DOI: 10.1140/epjd/e2015-60106-8
|View full text |Cite
|
Sign up to set email alerts
|

On the use of additivity rules to estimate electron production cross sections in proton-biomolecule collisions

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: On the use of additivity rules to estimate electron production cross sections in proton-biomolecule collisions. Abstract. Additivity rules are employed to estimate electron production cross sections for proton collisions with nucleobases and amino acids, using as input experimental data for proton collisions with atoms and small molecules. Cross sections (total and single differential, in electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…3 and appear to be somewhat lower than the electron-impact measurements of [25]. If we multiply the latter by a factor of 0.75 they almost perfectly match the proton data point at E = 1 MeV, which is well described by most of the theoretical calculations included in , IMM-AR [31]; experiments: Iriki11 [29,30], Rahman16 [25] for electron impact using equivelocity conversion, Rahman75% are the data of [25] multiplied by 0.75.…”
Section: Resultsmentioning
confidence: 52%
“…3 and appear to be somewhat lower than the electron-impact measurements of [25]. If we multiply the latter by a factor of 0.75 they almost perfectly match the proton data point at E = 1 MeV, which is well described by most of the theoretical calculations included in , IMM-AR [31]; experiments: Iriki11 [29,30], Rahman16 [25] for electron impact using equivelocity conversion, Rahman75% are the data of [25] multiplied by 0.75.…”
Section: Resultsmentioning
confidence: 52%
“…This is a desirable property since the IAM-AR is known to give fairly accurate results in the high-impact-energy regime in which capture and ionization cross sections are small and geometrical overlap is negligible. Toward lower energies, capture and ionization become stronger and the IAM-AR tends to overestimate experimental data [17,21]. In applications to proton collisions from medium-sized molecules such as H 2 O and from larger water, neon, and carbon clusters we have found that geometrical overlap does occur at these lower energies and leads to significant cross-section reductions [21,22].…”
Section: Introductionmentioning
confidence: 91%
“…Normally, atomic building blocks are used and the description is referred to as independent-atom-model (IAM)-AR. In a recent work it was argued that one can also start from small molecular constituents to assemble the ionization cross section of a larger molecule [17]. A caveat of this independent-molecule-model (IMM)-AR is that there are usually many different ways to decompose a given molecule into molecular building blocks and depending on which ansatz is used the resulting cross section may vary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper of Hilgers et al [23] presents the results of a simulation of an ion-counting nanodosimeter. Theoretical studies of ionization of biomolecules with protons are reported by Paredes et al [24]. Finally, a theoretical analysis of secondary electron production in liquid water sensitized with carbon nanoparticles is reprorted by Verkhovtsev et al [9].…”
Section: Introductionmentioning
confidence: 99%